Unilateral antibiotic-induced acute eosinophilic pneumonia on the operative side after surgery for primary lung cancer: a case report - Yasufumi Goda; Tsuyoshi Shoji; Hiromichi Katakura (Surgical Case Reports)
Abstract Background Acute eosinophilic pneumonia (AEP) is a rare idiopathic lung disease characterized by pulmonary eosinophilia. The epidemiology of AEP remains understudied; however, past reports have reported that AEP can be caused by an allergic reaction to medications, such as antibiotics or inhaled antigens, such as tobacco smoke. AEP usually occurs bilaterally. However, we encountered an unusual case of antibiotic-induced eosinophilic pneumonia showing unilateral consolidation just on the operative side, which was initially diagnosed as postoperative bacterial pneumonia and treated with antibiotic therapy. The prescribed antibiotics paradoxically provoked AEP and worsened the patient’s condition. Here, we report this antibiotic-induced AEP case showing unilateral consolidation only on the operative side which could be triggered by surgery for primary lung cancer. Case presentation A 74-year-old man underwent right upper lobectomy for lung adenocarcinoma. On postoperative day (POD) 9, an interstitial shadow appeared in the right lower lung field of the chest radiographs, along with a fever of 38.5 °C, dyspnea needing oxygen supplementation, and increased purulent sputum production, suggesting postoperative bacterial pneumonia. Despite administration of the broad-spectrum antibiotic, meropenem, the fever did not improve, and pulmonary opacity gradually worsened. Blood analysis showed increased peripheral eosinophils at 1182/mm3. The meropenem treatment was discontinued and bronchoscopy was performed for further evaluation, and the bronchoalveolar lavage fluid assessment showed a remarkable increase in the eosinophil population (51%). The drug lymphocyte stimulation test (DLST) for meropenem was positive. We diagnosed the patient with antibiotic-induced unilateral AEP, after which corticosteroid treatment was initiated. The patient subsequently improved and the infiltration in the right lower lung field completely disappeared. The patient was discharged on POD 43 without oxygen supplementation and is doing well without tumor recurrence 16 months after the surgery. Conclusions Unilateral drug-induced AEP is rare. Nonetheless, it should be recognized as a differential diagnosis of postoperative pneumonia even in cases of a unilateral radiographic infiltration, because the lung operation itself could trigger this type of AEP.